Just joking 2 : 300 hilarious jokes about everything, including tongue twisters, riddles, and more! - National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2012)
A collection of three-hundred jokes, riddles, and tongue twisters for kids from National Geographic, including photographs.
Includes indexes.
Booklist, January 2013.
2.6
3-6
590L
Keywords: Wit and humor, Juvenile; Riddles, Juvenile; Tongue twisters -- Juvenile literature; Animals -- Pictorial works -- Juvenile literature; Jokes; Riddles; Tongue twisters; Animals -- Pictorial works; Jokes; Riddles; Tongue twisters; Animals -- Pictorial works; Wit and humor; Jokes